Diagnostic Efficacy and Prognostic Recurrence Prediction Effect of Regulatory T Cells plus TGF-β1 in Pediatric Patients with Allergic Rhinitis and Concurrent Adenoid Hypertrophy - Ning,; Chen, Weibin; Guo, Lingyun; Huang, Yongping (Journal of Medical Biochemistry, 2025)
Objective: The co-occurrence of adenoid hypertrophy (AH) and allergic rhinitis (AR) is known to be linked to immune microenvironment disruptions. This research was designed to assess how regulatory T cells (Treg) and transforming growth factor-β1 (TGF-β1) perform in diagnosing AH in pediatric AR cases and in predicting the likelihood of post-treatment recurrence.Methods: From February 2023 to June 2024, 127 children diagnosed with AR alone (AR group) and 134 children with AR-AH comorbidity (AR+AH group) were recruited. All participants were followed prospectively for a 12-month period. Peripheral blood Treg counts were measured using flow cytometry, while serum TGF-β1 concentrations were determined via enzyme-linked immunosorbent assay (ELISA). Diagnostic effectiveness was evaluated using receiver operating characteristic (ROC) curves. A Logistic regression model was developed to forecast recurrence risk, with model parameters refined by incorporating relevant clinical features.Results: AR+AH cases exhibited statistically lower Treg counts and TGF-β1 levels than their AR counterparts (P